2022
DOI: 10.1007/s00289-022-04400-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of calcium carbonate-quince bio-composite for programmed and on-demand drug release of paracetamol at target site: a green chemistry approach

Abstract: In this study, an inorganic–organic composite system was developed through biomineralization of calcium carbonate in the quince-seed mucilage-based hydrogel. Drug-polymer interactions were studied by FTIR, DSC, XRD and SEM analysis. The water absorption capacity was calculated by swelling index. Drug release was determined at various pH. Several in vitro kinetic models were applied to observe drug release behaviour. Studies of drug-polymer interactions and particle flow characteristics of the developed composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…DSC allows to assess the temperatures at which characteristic endothermic and exothermic transitions occur and that are specific for a certain substance and its structure. These can indicate the melting point of the sample or more generally a state transition (e.g., a rubbery-glass transition) and its purity, and confirm any interactions between samples in mixture or neostructured in a carrier system [103][104][105].…”
Section: Encapsulation Yield and Solid-state Characterizationmentioning
confidence: 70%
See 1 more Smart Citation
“…DSC allows to assess the temperatures at which characteristic endothermic and exothermic transitions occur and that are specific for a certain substance and its structure. These can indicate the melting point of the sample or more generally a state transition (e.g., a rubbery-glass transition) and its purity, and confirm any interactions between samples in mixture or neostructured in a carrier system [103][104][105].…”
Section: Encapsulation Yield and Solid-state Characterizationmentioning
confidence: 70%
“…), number and type of simulated environments (mouth, stomach, intestine, colon and any other specific sections) and their specific reference parameters (simulated environment in empty or fed conditions, pH, travel time, volumes and fluid composition, thus presence or absence of specific enzymes, surfactants, salts, etc.) [7,46,104,[116][117][118][119][120]. Added to this is the common research effort to develop in vitro dissolution/release equipment/protocols with increasing significance and predictivity of the in vivo process [121][122][123].…”
Section: In Vitro Release Testingmentioning
confidence: 99%
“…The prepared coreshell drug carrier can delay the rate of drug release. Kulsoom et al [28] reported on the development of a composite system prepared by biomineralization of calcium carbonate in mucilage obtained from seeds of naturally occurring quince plants. The developed composite showed restricted release of paracetamol in the acidic media, while a controlled fashion of drug release was observed in the basic media over a period of 12 h. Study outcomes suggested that the developed composite can be considered a novel drug carrier system for oral colon-targeted delivery of hydrophilic/hydrophobic drugs.…”
Section: Calcium Carbonate As a Controlled-release Drug Carriermentioning
confidence: 99%
“…Excess AP can cause acute liver damage. Moreover, AP is one of the most commonly used medicines causing acute liver injury and is the leading cause of acute liver failure as its elimination half-life is approximately 2 h for therapeutic doses [3][4][5][6]. Regular use of AP is essential for analgesic and antipyretic support in patients with fever and discomfort.…”
Section: Introductionmentioning
confidence: 99%